Inhibition of the P3–O3 phase transition via local symmetry tuning in P3-type layered cathodes for ultra-stable sodium storage. Issue 6 (20th January 2023) - Zhou, Ya-Nan; Xiao, Zichun; Han, Duzhao; Wang, Suning; Chen, Jinniu; Tang, Wei; Yang, Mingyu; Shao, Le; Shu, Chengyong; Hua, Weibo; Zhou, Dezhong; Wu, Yuping
Abstract : We reconfigure the sodiation/desodiation process of P3-type layered cathodes by a local symmetry tuning strategy to enhance their stability. The cathodes exhibit long-term cycling stability with a higher capacity retention of 74% after 2000 cycles at 1C. Abstract : Sodium-deficient layered oxide cathode materials such as P3-type Na2/3 Ni1/3 Mn2/3 O2 (P3-NaNM) usually suffer from different kinds of Na + /vacancy ordering and phase transitions upon Na + extraction/insertion, which result in inferior rate capability and rapid capacity fading over prolonged cycling. To address these challenges, a highly reversible P3-Na2/3 Li1/9 Ni5/18 Mn1/2 Ti1/6 O2 (P3-NaLNMT) cathode was designed and developed via local symmetry tuning, i.e. adding Na–O–Ti and Na–O–Li configurations. In situ synchrotron-based X-ray diffraction results clearly demonstrate that P3-NaLNMT undergoes a single phase solid-solution reaction as Ni 2+ /Ni 3.2+ redox occurs upon cycling, accompanied by a small variation of unit-cell volume (−2.2%). In contrast, a sluggish phase transformation from the P3 to O3 structure during the discharge process is revealed in P3-NaNM at 0.2C. As a consequence, P3-NaLNMT exhibits an outstanding electrochemical performance and robust structural stability. Specifically, a high-capacity retention of 74% can be achieved in P3-NaLNMT after 2000 cycles at 1C compared to 51% for P3-NaNM after 730 cycles. Moreover, the hard carbon//P3-NaLNMT full battery exhibits a stable midpoint voltage after 500 cycles at 1C. The insights presented in this work pave the way for further designing of cathode materials with even higher performance via phase transition tailoring.